HUBUNGAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI MELALUI PERILAKU KEUANGAN SEBAGAI VARIABEL INTERVENING PADA KELUARGA DI DUSUN SIDOMULYO DESA SUMBERWARU - Maghfiroh, Shofiyatul; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Family finances are the most important thing in building a prosperous family, by managing family finances properly in order to avoid financial problems and be able to make financial decisions in the future. The purpose of this study was to analyze and examine the effect of financial literacy on investmenst decisions in families through financial behavior. The population in this study were families in sidomulyo Hamlet, Sumberwaru Village. The sampling technique was determined by non probability sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that financial literacy has a significant positive effect on financial behavior, financial literacy has a significant positive effect on investment decisions, financial behavior has a significant but negative effect on investment decisions. The result of the indirect effect hypothesis test show that financial literacy on investmenst decisions through financial behavior has a significant negative effect.